Update on R-loops in genomic integrity: Formation, functions, and implications for human diseases - Min Zhu; Xinyu Wang; Hongchang Zhao; Zhenjie Wang (Genes and Diseases)
R-loops, three-strand nucleic acid structures, have emerged as crucial players in various physiological processes, including the regulation of gene expression, DNA replication, and class switch recombination. However, their presence also poses a significant threat to genome stability. A particularly challenging aspect is understanding the dynamic balance between R-loops' “light” and “dark” sites, especially concerning maintaining genome integrity. The complex and multifaceted roles of R-loops in genome stability necessitate a deeper understanding. This review offers a comprehensive exploration of the formation, resolution, and implications of R-loops, particularly in the context of DNA damage and human disease. We delve into the dualistic nature of R-loops, highlighting their role in DNA damage response and repair, and discuss the therapeutic potential arising from our evolving understanding of these enigmatic entities. Emphasizing recent advancements and unresolved questions, this review aims to provide a cohesive overview of R-loops, inviting further inquiry and investigation into their complex biological significance.